Kurt Lewin (1890–1947) – in the eyes of his biographers - Zeidler, Włodzisław (Studia Psychologica: Theoria et praxis, 2021)
Kurt Lewin's views and work have had, and continue to have, a fascinating influence on many authors who write about his life's journey and work, based on their own knowledge and the state of research into that work. Kurt Lewin has a permanent place in the history of psychology, but despite this, depending on the author's point of view, images of his work vary. Following in the footsteps of Graumann (1992/2007), this paper examines his view that 20th century psychology was not prepared to receive and understand the works of Kurt Lewin. Graumann's position is justified by the fact that individual biographers limited their focus on Lewin's work to either the „Berlin period” or that in the United States. By doing so, they blurred the complexity and clarity of the picture of his life space, which, however, already began in Mogilno and Poznan.